EMBRYO RECONSTRUCTION BY TRANSPLANTATION OF THE DONOR INNER CELL MASS TO THE RECIPIENT BOVINE BLASTOCYST - ARIEF BOEDIONO (SEAMEO BIOTROP, 2006)
In an attempt to produce the interspecies embryo transfer, this study was conducted to evaluate the efficacy of the production of reconstructed blastocyst by transferring the donor ICM into the recipient trophoblast. ICM cells were isolated from the donor blastocyst by immunosurgery method. Zona-free blastocysts were incubated in the medium (TCM-199) containing 20% of the heat-inactivated rabbit anti-bovine-serum. The embryo reconstruction was produced by three different methods. Recipient blastocyst was maintained on the holding pipette by gentle suction, with the ICM in a 9 o'clock position to have the possibility of developing incorporate ICMs (Method I), the ICM was in a 3 o'clock position to break the original ICM during injection (Method 2); cutting the original recipient ICM followed by insertion of the donor ICM (Method 3). Reconstructed blastocysts were then cultured overnight and examined morphologically according to the re-expansion of the reconstructed blastocyst with or without developed donor ICM. According to morphological observation in this study, 37.9% of the reconstructed blastocyst developed with the incorporation of two ICM originally from recipient and donor (Method I), 66.7% of the reconstructed blastocysts developed with a single ICM (Method 2), and 80.0% of the reconstructed blastocyst developed from the ICM originally from donor ICM (Method 3). These results showed that the reconstructed blastocyst is better produced by cutting the original recipient ICM followed by the insertion of the donor ICM (Method 3).Key words: embryo reconstruction, immunosurgery, ICM transfer, bovine.